2013
DOI: 10.1371/journal.pone.0061083
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of PBP1 by β-lactams Determines recA/SOS Response Activation in Heterogeneous MRSA Clinical Strains

Abstract: The SOS response, a conserved regulatory network in bacteria that is induced in response to DNA damage, has been shown to be associated with the emergence of resistance to antibiotics. Previously, we demonstrated that heterogeneous (HeR) MRSA strains, when exposed to sub-inhibitory concentrations of oxacillin, were able to express a homogeneous high level of resistance (HoR). Moreover, we showed that oxacillin appeared to be the triggering factor of a β-lactam-mediated SOS response through lexA/recA regulators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 55 publications
6
24
0
Order By: Relevance
“…Previous work has suggested that the degree to which different ␤-lactams potentiate the anti-MRSA activity of DAP may be associated with the relative affinity for PBP1 (13). This specific differential effect echoes other recent studies that observed increased toxin expression (12) and induction of DNA repair systems (14) upon inhibition of PBP1 but not upon inhibition of other PBPs (12,(15)(16)(17).…”
supporting
confidence: 62%
“…Previous work has suggested that the degree to which different ␤-lactams potentiate the anti-MRSA activity of DAP may be associated with the relative affinity for PBP1 (13). This specific differential effect echoes other recent studies that observed increased toxin expression (12) and induction of DNA repair systems (14) upon inhibition of PBP1 but not upon inhibition of other PBPs (12,(15)(16)(17).…”
supporting
confidence: 62%
“…RNA extractions for real-time reverse transcription-PCR (RT-PCR) analysis were performed as previously described (17). Total RNA was extracted using an RNeasy isolation kit (Qiagen); all RNA samples were analyzed by A 260 /A 280 spectrophotometry to assess concentration and integrity and cleaned of potential DNA contamination by treating them with DNase per manufacturer recommendations (Ambion, Inc., Life Technologies/Thermo Fisher, Austin, TX).…”
Section: Methodsmentioning
confidence: 99%
“…We used a wax worm model to investigate whether CPT therapy regimens have enhanced in vivo efficacy against clinical HeR-and HoR-MRSA compared with the efficacies of other ␤-lactam regimens, including IPM, NAF, and FOX. Larvae of the greater wax moth (Galleria mellonella) have recently been used as an alternative to vertebrates as a model host for studying pathogenic microbes, virulence, and therapeutic regimens (21)(22)(23), including the assessment of the efficacy of antistaphylococcal agents (17,20). G. mellonella larvae possess an immune system relatively homologous to the innate immune system of vertebrates, a digestive tract, a loosely organized muscular system, a biosynthetic fat body, and hemolymph that, analogous to blood, transports nutrients, hemocytes, and immune molecules.…”
Section: In Vitro Activity Of Cpt Against Clinical Mrsa and Her-mrsa mentioning
confidence: 99%
“…Increased expression of the agr (accessory gene regulator) system during HeR-HoR selection was required to tightly modulate SOS-mediated mutation rates, which then led to full expression of homogeneous oxacillin resistance in very heterogeneous clinical MRSA strains (130). The PBP1 protein played a role in SOS-mediated RecA activation and HeR-HoR selection (131). Conversely, a mutation in the less resistant cells of a heterogeneous population seemed to be responsible for their increased susceptibility.…”
Section: Heteroresistance To ␤-Lactamsmentioning
confidence: 99%